FEMINIST CRITICISM: FEMALE REPRESENTATIONS IN JANE AUSTEN’S NOVELS (ELIZABETH BENNET & EMMA WOODHOUSE). - Kenjaboyeva O`g`iljon To`xtaboy qizi; Ne'matova Madina Baxtiyor qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article explores feminist criticism in Jane Austen’s novels through an analysis of two central female characters: Elizabeth Bennet from Pride and Prejudice and Emma Woodhouse from Emma. It examines how Austen presents intelligent, independent-minded women who challenge the restrictive gender norms of the 19th century. The study highlights how Elizabeth defies patriarchal expectations through wit, moral agency, and refusal to marry without affection, while Emma represents a woman with social power who learns self-awareness and autonomy. The article concludes that Austen’s heroines reflect early feminist perspectives by asserting women’s emotional, intellectual, and moral independence within the constraints of their social environment.